Combining the Marangoni Effect and the pH‐Responsive Superhydrophobicity–Superhydrophilicity Transition to Biomimic the Locomotion Process of the Beetles of Genus Stenus. Issue 15 (1st March 2013) - Xiao, Meng; Cheng, Mengjiao; Zhang, Yajun; Shi, Feng
<x xml:space="preserve">Abstract</x> A functional device to mimic the beetles of the genus Stenus is fabricated. A superhydrophobic hull is employed to replace the body of the beetles, with an attached reservoir to store low‐surface‐energy compounds to mimic the beetle's pygidial gland, and a pH‐responsive mesh acts as its gland end, whose locomotion from static to mobile can respond to the pH value transformation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>